A computational work on a three dimensional analysis of natural convection and entropy generation in nanofluid filled enclosures with triangular solid insert at the corners - Kolsi, Lioua; Öztop, Hakan Fehmi; Alghamdi, Abdulaziz; Abu-Hamdeh, Nidal; Borjini, Mohamed Naceur; Ben Aissia, Habib (Elsevier Science Bv, 2016)
Laminar three dimensional flow and heat transfer in a nanofluid filled cavity with solid insert at the corners is analyzed computationaly by using finite volume method. Entropy generation is also presented from the obtained results of velocity and temperature values. In order to simulate nanofluids, an in-house numerical method was developed based on the solution of three dimensional solution of Navier-Stokes equations.Three cases are studied based on number and location of solid inserts. Effects of Rayleigh number (10(4) <= Ra <= 10(6)), nanoparticle volume fraction (0 <= phi <= 0.15) and thermal conductivity ratio (0.01 <= Rc <= 100) are analyzed on natural convection and entropy generation. It is observed that a three dimensional solution brings a more understanding work for the study. Higher heat transfer and entropy generation are observed in the case of nanoparticle addition into base fluid. In any case, partitions can be used as a control element for heat and fluid flow and energy consumption. (c) 2016 Elsevier B.V. All rights reserved.
Keywords: Nanofluids; Natural convection; Triangular obstacle; 3D cavity